Effects of the Characteristics and Duration of Chronic Pain on Psychosomatic Function in the Community-Dwelling Elderly Population - Hida, Mitsumasa (Pain Res Manag, 2020)
Catastrophic thinking is related to pain intensity and the degree of disability and influences pain care significantly. However, only few studies have investigated the impact of catastrophic thinking on chronic pain (CP) in the community-dwelling elderly population. This study aimed to evaluate the characteristics of CP in the community-dwelling elderly population and to investigate the effects of different periods of CP on cognitive and psychological functions. A total of 187 community-dwelling elderly people met the inclusion criteria and were included in this cross-sectional study. The survey items included demographic data (age and gender), pain-related questionnaires, psychological and cognitive functions, and sleep status. The duration of CP was investigated using three categories: no pain and pain for ≤1 year and ≥1 year. A logistic regression analysis was performed to identify the factors most strongly associated with the presence of CP. The difference in each assessment was compared according to duration of CP among the three groups and analyzed using the chi-square test, Kruskal–Wallis test, and one-way analysis of variance. The PCS scores and depression scores were significantly higher in long duration of CP compared with no pain and pain for ≤1 year. The present study is consistent with the fear-avoidance model and was concluded that community-dwelling elderly people with CP are depressive and tend to magnify their pain with long duration of CP.